TERRA ARRASADA, UTOPIAS DIGITAIS: HISTÓRIA E IDEOLOGIA NO VALE DO SILÍCIO - Ceolin, Arnon Manhães (2021)
In the so-called Silicon Valley, large corporations of the computer hardware and software industry and associated to the Internet emerged and expanded, such as Microsoft, Apple, Intel and Google. More recently, Facebook, Twitter, and Uber have appeared, all of them managers of decisive technologies for the reproduction of contemporary capitalist society. What this work analyzes, at first, is the system of libertarian ideas that emerged along with the rise of the Internet and personal computers in the 1990s, ideas that remains active to this day for the purpose of political legitimization of these corporations and their respective technologies. Here is what is called Silicon cyberlibertarianism, an ideology formed by the technological determinism characteristic of technological managers added to an amalgamation of fragments of the utopias of the communalist, countercultural and New Left movements with injunctives of US laissez-faire libertarianism. To better describe this ideology, we did a bibliographic research about five phenomenons that synthesize the origin of cyberlibertarianism in Silicon and that are still influential in contemporaneity: the cyberspatial colonialism of John Perry Barlow and the Electronic Frontier Foundation (EFF), the media optimism of Louis Rossetto and Kevin Kelly through WIRED magazine, the Burning Man festival's gift economy, Timothy May's cypherpunk crypto-anarchism, and the entrepreneurial apology of George Gilder and the Progress & Freedom Foundation (PFF). In the second part of the dissertation, also through a bibliographic research, some of the assumptions of Silicon cyberlibertarianism are called into question and a window is opened for the analysis of the historical formation of Silicon Valley as a strategic instrument for the defense of US state sovereignty in a century marked by world wars. In this sense, we work with the thesis that the formation of the technological system in Silicon Valley derived from a broad effort of mobilization of public war budgets, a process that remits the beginnings of the western colonization and the territorialization of the californian state in the 19th century and which extends throughout the 20th century, when the most importante angel investor of Silicon Valley emerged: the military-industrial complex.